Femvertising and COVID-19—What Did Brand Owners Broadcast during the Lockdown? - Jambrino-Maldonado, Carmen; Iglesias-Sánchez, Patricia Pilar; De-las-Heras-Pedrosa, Carlos; Olivares Delgado, Fernando; Benlloch-Osuna, María T. (MDPI, 2023)
he aim of this study was to analyze, from a gender perspective, advertising broadcasts during a time of crisis. A holistic perspective of the stereotypes, roles, professions, and gender relations represented is offered by utilizing a content analysis of all the advertisements and their corresponding images during broadcast. Methods: a content analysis of 20 variables was conducted; of these, 7 variables were obtained from under the gender perspective of 1.350 images, corresponding to 71 audiovisual spots on YouTube that were broadcasted during the lockdown. Results: this analysis showed the special sensitivity of advertisers when balancing male and female presences, and in projecting an equitable and co-responsible vision between both genders, with special emphasis on gender professions, teleworking, and childcare. Corporate advertising predominates over commercial advertising, which may explain why the discourse and images blur inequalities and imbalances with respect to official statistics. Conclusions: advertisers seem to have noticed the strategic role of introducing gender perspectives into advertising, thus assuming a more social function that better connects them with today’s society while also supporting the advances and challenges of equal opportunities.
Keywords: You Tube; Rol de Género; Feminismo; Gender approach; Advertising; Femvertising; Women’s representation; Gender roles; Digital media